CHILD PROTECTION IN INDONESIA IN THE PERSPECTIVE OF NATIONAL LAW AND ISLAMIC LAW - Madnur, Madnur; Irfan, M. Nurul (Journal of Law and Policy Transformation, 2023)
This qualitative research discusses child protection in terms of regulations in force in Indonesia and Islamic law. Child protection is a particular discussion because it is an integral part of the nation; protecting children means protecting the nation's generation. In Indonesia itself, there are various formulations of laws and regulations that regulate child protection. Meanwhile, efforts to protect children in Islamic law are part of implementing maqasid sharia, which upholds human values. To realize this, severe sanctions have been stipulated in national and Islamic law for perpetrators of acts of violence against children, aiming to provide a deterrent and deterrent effect on perpetrators of child crimes. However, these sanctions are still being debated in the community. Regardless of all that, efforts to guarantee child protection in preventing violence against children must continue whenever and wherever.